1966
DOI: 10.1677/joe.0.0340479
|View full text |Cite
|
Sign up to set email alerts
|

The Human Adrenal Gland With Special Reference to the Vasculature

Abstract: SUMMARY The internal anatomy, particularly the vasculature, of the human adrenal was investigated with the help of three-dimensional reconstruction models supplemented by stereo-angiography. A definite pattern of positional relationship was shown to exist between the cortex, medulla and venous drainage, and on this basis the adrenal should be considered as a tripartite structure consisting of a head, a body and a tail region. The disposition of the longitudinal muscle bundles in the adrenal veins follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

1966
1966
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 0 publications
4
75
0
2
Order By: Relevance
“…The filling of the capsular veins appears to be mainly but not exclusively dependent on flow from the venae comites of the medullary arteries (Fig. 5) evidence to support the suggestion of Dobbie and Symington (1966) that the biosynthetic products of the zonae fasciculata and reticularis can exit via the veins or arteries rather than or in addition to the central vein is the demonstrated link between some inner cortical sinusoids and the venae comites of the medullary arteries (Fig. 5).…”
Section: Dog Adrenalssupporting
confidence: 66%
See 3 more Smart Citations
“…The filling of the capsular veins appears to be mainly but not exclusively dependent on flow from the venae comites of the medullary arteries (Fig. 5) evidence to support the suggestion of Dobbie and Symington (1966) that the biosynthetic products of the zonae fasciculata and reticularis can exit via the veins or arteries rather than or in addition to the central vein is the demonstrated link between some inner cortical sinusoids and the venae comites of the medullary arteries (Fig. 5).…”
Section: Dog Adrenalssupporting
confidence: 66%
“…These descriptions give the impression that there is one circulatory system in the adrenal gland although this gland is composed of two district tissues. The present concern is with the pattern of venous drainage from the cortex and medulla and the investigation into the hypothesis that a portal system exists in both directions (Vogt 1944;Dobbie and Symington 1966).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To a lesser extent, a difference was also detected in adrenal body size. Dobbie and Symington (15) showed that the limbs of the adrenal gland consist predominantly of adrenal cortical tissue with little or no medullary tissue, which is maximal in the body. Enlargement of the limbs indicates adrenal cortical expansion and our study therefore confirms previous reports that adrenocortical hyperplasia is part of the MEN1 syndrome.…”
Section: Discussionmentioning
confidence: 99%